2021
DOI: 10.3389/fphys.2021.775029
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-23-Klotho Axis in Cardiorenal Syndrome: Mediators and Potential Therapeutic Targets

Abstract: Cardiorenal syndrome (CRS) is a complex disorder that refers to the category of acute or chronic kidney diseases that induce cardiovascular disease, and inversely, acute or chronic heart diseases that provoke kidney dysfunction. There is a close relationship between renal and cardiovascular disease, possibly due to the presence of common risk factors for both diseases. Thus, it is well known that renal diseases are associated with increased risk of developing cardiovascular disease, suffering cardiac events an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 196 publications
(263 reference statements)
0
8
0
Order By: Relevance
“…In order to exert its renal effects and contribute to the development of the cardiorenal syndrome, FGF-23 needs to bind to certain receptors in the presence of a co-factor called Klotho, promoting phosphaturia. FGF-23 may also have direct effects on the heart, in a Klotho-independent interaction [ 74 ]. Experimental studies suggested that, in the heart, FGF-23 may contribute to myocardial hypertrophy, endothelial dysfunction and atherosclerosis, and, therefore, may be used as a biomarker of CV disease [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to exert its renal effects and contribute to the development of the cardiorenal syndrome, FGF-23 needs to bind to certain receptors in the presence of a co-factor called Klotho, promoting phosphaturia. FGF-23 may also have direct effects on the heart, in a Klotho-independent interaction [ 74 ]. Experimental studies suggested that, in the heart, FGF-23 may contribute to myocardial hypertrophy, endothelial dysfunction and atherosclerosis, and, therefore, may be used as a biomarker of CV disease [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in mineral metabolism, including those involving klotho deficiency and increased circulating FGF23 levels, have been linked to kidney disease. However, they may also have direct cardiovascular effects in patients in the different stages of CKD and AKI [ 10 ]. At an experimental level, it has been recently described that ventricular adult cardiomyocytes show relevant functional damage in the first hours after AKI where kidney klotho expression drops significantly [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that serum levels of klotho decrease with aging and it is also associated with several typical age-related disorders such as diabetes, vascular calcification, atherosclerosis, cardiovascular and renal diseases [ 4 , 6 , 9 ]. In the kidney, low circulating plasma soluble klotho levels have been correlated with worsening renal function in chronic kidney disease (CKD) and end-stage renal disease (ESRD) as well as in acute kidney injury (AKI) [ 10 ]. Furthermore, low soluble klotho levels are associated with arterial stiffness in CKD, increased cardiovascular mortality rate in haemodialysis and cardiovascular disease risk factors in older adults [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, HDAC4 may be a critical mediator in regulating the depression of Klotho during the acute phase and perhaps chronic phase of renal injury following UUO. Since Klotho functions as a coreceptor of FGF receptors (FGFRs) to activate a specific fibroblast growth factor 23 (FGF23) signal pathway and FGF23 exerts its biological effects in a Klotho-dependent manner ( Lu and Hu, 2017 ; Navarro-Garcia et al, 2021 ), it is possible that HDAC4-mediated regulation of Klotho may also indirectly influence the biological functions of FGF23 such as mineral homeostasis and CKD-related bone disorders and cardiovascular problems. Furthermore, an investigation is needed to address these issues.…”
Section: Discussionmentioning
confidence: 99%